Peer Violence During Adolescence: A Systematic Review of Instruments for Spanish Speakers - González Moreno, Alba (2022)
Peer violence that occurs in adolescence is a problem that has negative effects on all individuals involved. The main objective of this systematic review was to identify the different existing instruments to assess violence among adolescents in a Spanish-speaking context. The methodology used consisted of searching for documents in the Web of Science, Scopus, Eric, Dialnet Plus and Ebsco databases using the search formula "violence AND questionnaire AND adolescents" in Spanish and English. The results have included a total of 14 articles that show a wide variety of instruments for evaluating violence between peers that have been classified into two sections: Instruments for evaluating school violence and instruments for evaluating violence in a relationship. All the questionnaires have been validated in the adolescent population, which shows that they are good tools that allow identifying the existence of violent behaviors among young people, as well as which are the most repeated behaviors. Peer violence should be investigated to establish a series of educational strategies that allow the reduction of this problem in the classroom.